CULTIVATING LEADERSHIP IN UNIVERSITY STUDENTS THROUGH SOCIOCULTURAL ACTIVITIES: ANALYSIS AND EMPERICAL STUDY - Palatkina; Tarasova; Dzhangaziyeva; Sharonov; Podlipalin; Palatkin (Revista Inclusiones, 2019)
Authors examine factors, psychological and pedagogical conditions, objective and subjective factors for student leadership development. Main methods and techniques for cultivating student leadership have been identified. These are interactive methods, case studies, masterclasses, formative techniques, innovative techniques, educational techniques. The article presents an empirical study of student leadership levels in the Astrakhan State University and the Astrakhan State Medical University. To meet the objectives, mathematical-statistical data-processing methods were applied, including calculation of descriptive statistics, the Kolmogorov-Smirnov one-sample test, the Student’s test for dependent and independent samples, the Mann-Whitney test, the Wilcoxon test. The main results of the experiment are that the students’ leadership level in the experimental group has changed as a result of the students’ participation in business games, teamwork, role plays, discussions, engagement in the university public activities, and through students’ enriching their own leadership experience via extracurricular activities. Summing up the results, we consider it necessary to note the following: the complexity of the leadership phenomenon, and the multivariety of its components, factors, and conditions of its dynamics, require to select methods for each of its components separately.